58.6k views
0 votes
Type the correct answer in each box. Use numerals instead of words.

Consider this expression.
- 4x2 + 2x - 5(1 + x)
What expression is equivalent to the given expression?

1 Answer

1 vote

Answer:

4x² + 3x + 5

Explanation:

Given:

- 4x² + 2x - 5(1 + x)

Open parenthesis

= - 4x² + 2x - 5 - 5x

= - 4x² + 2x - 5x - 5

= - 4x² - 3x - 5

Multiply through by -1

= - 1( - 4x² - 3x - 5)

= 4x² + 3x + 5

Write

4 in the first box

3 in the second box

5 in the third box

Type the correct answer in each box. Use numerals instead of words. Consider this-example-1
User Cyrlop
by
4.9k points